’n Postliberale venster op die preek - Nell, I. (Verbum et ecclesia, 1999)
A Postliberal view on the sermon Over the same period that homiletics has enjoyed a resurgence, mainline Protestant churches have been in decline. The multiplication of preaching theories and resources has taken place alongside a growing concern about the life and future of the church. Despite all the theories and resources many local pastors know something is lacking in their preaching. They've tried inductive preaching, story preaching, dialogue sermons, and homiletical plots. While these new methods have been exciting for the moment, many preachers sense something is still missing. It will be argued that it is partly due to the absence of thorough theological reflection.